Indonesia’s Motivations for Signing of the Indonesia-Chile Comprehensive Economic Partnership Agreement (IC-CEPA) - Musfiroh, Musfiroh (Universitas Cenderawasih, 2024)
Free Trade Agreements (FTAs) have recently become a recognized global trend which continues to increase in number as they offer ease of access to markets and reduction of trade barriers. Almost all countries involved in FTAs pursue their national interests, particularly economic ones, and Indonesia and Chile are no exception. This topic is interesting to scrutinize because the geographical factors of the two countries are quite far distant, and there were larger economic partners for Indonesia in South America (Brazil and Argentina) than Chile in regards to the establishment of a Free Trade Agreement. This article uses the approach of Solis and Katada, international relations’ experts, which looks at it with a broader view. The approach emphasizes the establishment of international economic cooperation not only based on economic interests or caused solely on geographical proximity. Yet still, even economic motives are considered, other motives like political motive cannot be denied. The results of this study indicate that Indonesia’s involvement in IC-CEPA is not only based on economic motives, there are other motives such as politics (raise international status) which cannot be ignored.KEYWORDSFree Trade Agreement; Chile; IC-CEPA; Indonesia; Trade cooperation